Prediction of individual automobile reported but not settled claim reserves for bodily injuries in the context of Solvency II - Ayuso Gutiérrez, M. Mercedes; Santolino Prieto, Miguel Á. (Journal of Quantitative Methods for Economics and Business Administration, 2016)
Automobile bodily injury (BI) claims remain unsettled for a long time after the accident. The estimation of an accurate reserve for Reported but not Settled claims is therefore vital for insurers. In accordance with the recommendation included in the Solvency II project, a statistical model is implemented for reserve estimation. Lognormality on empirical cost data is observed for different levels of BI severity. The individual claim provision is estimated by allocating the expected mean compensation for the predicted severity of the victim’s injury, for which the upper bound is also computed. The severity is predicted by means of a heteroscedastic multiple choice model, because evidence has found that the variability in the latent severity of individuals travelling by car is not constant. It is shown that this methodology improves the accuracy of reserve estimation at all stages, as compared to the subjective assessment that has traditionally been made by practitioners.